2021
DOI: 10.1111/jocs.15277
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term renal function after venoarterial extracorporeal membrane oxygenation

Abstract: Background The utilization of venoarterial extracorporeal membrane oxygenation (VA‐ECMO) as a life‐supporting therapy has increased exponentially over the last decade. As more patients receive and survive ECMO, there are a number of unanswered clinical questions about their long‐term prognosis and organ function including the need for long‐term dialysis. Methods We aimed to utilize over 208 patient‐years of follow‐up data from our large institutional cohort of VA‐ECMO patients to determine the incidence of req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Categories delineating race or ethnicity varied markedly. Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Two large cohort studies from the Taiwan’s National Health Insurance Research Database including VV- and VA-ECMO patients revealed increased risks of CKD, ESKD, and all-cause mortality in AKI-RRT patients (mean follow-up 2.4 ± 2.5 years per patient) [ 10 , 28 ]. A study in VA-ECMO patients demonstrated 11% dialysis dependence (median follow-up 64 months in non-ESKD patients) and 51% prevalence of CKD at 1 year [ 29 ]. Another recent study of predominantly VA-ECMO survivors (80%) reported major adverse kidney events (median follow-up time 3.4 years) which include AKI, partial/no recovery at discharge, and RRT on the same date or after ECMO initiation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor, We recently reviewed the article "Long-term renal function after venoarterial extracorporeal membrane oxygenation" by Brian ayers MD et al 1 with deep interest. The article is well written, and the author's work is cherished and appreciated regarding this valuable topic.…”
Section: Funding : Nonementioning
confidence: 99%